Mechanical properties and fracture parameters of geopolymers based on cellulose nanocrystals from Typha sp. fibers. (December 2022) - Rahmawati, Cut; Aprilia, Sri; Saidi, Taufiq; Aulia, Teuku Budi; Amin, Amri; Ahmad, Jawad; Isleem, Haytham F.
Abstract: As an environmentally friendly material, geopolymers are demanded to have good mechanical and fracture strength. Therefore, this research studied the mechanical properties and fracture parameters of geopolymers based on cellulose nanocrystals (CNCs) from typha sp. fibers. The different percentages of CNCs studied were 0%, 1%, 2% and 3%. Various mechanical parameters were evaluated, such as compressive strength, flexural strength, fracture toughness, and direct tensile strength. Microstructures were also evaluated to strengthen the assessment, which included Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The results showed that using 1% CNCs was the most effective for improving the mechanical properties, fracture behavior, and microstructural of CNCs-based geopolymers. Using 1% CNCs in geopolymer showed maximum increases of 15.76% and 11.72%, respectively, for compressive strength and tensile strength. Meanwhile, using 1% of CNCs improved flexural strength and fracture toughness up to 3.36 times. The addition of more than 1% CNCs even decreased the mechanical properties of CNCs-based geopolymers. SEM also confirmed that the inclusion of 1% CNCs increased the microstructure and produced a denser structure, and FTIR showed the presence of Si–O–Al bonds. CNCs-based geopolymers from typha sp. fibers can improve mechanical properties and fracture parameters, thus being suitable for reinforcement material and feasible to apply to construction.